2009
DOI: 10.1111/j.1440-1789.2008.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic amyotrophic lateral sclerosis: Widespread multisystem degeneration with TDP‐43 pathology in a patient after long‐term survival on a respirator

Abstract: It has been reported that widespread multisystem degeneration can occur in patients with sporadic amyotrophic lateral sclerosis (SALS) who have survived for long periods with artificial respiratory support (ARS). We report a case of SALS of 8 years and 8 months duration in a 71-year-old woman, who received ARS for 7 years and 8 months. In this patient, the symptoms at the early stage were those of typical ALS, and a totally locked-in state with frontal lobe atrophy appeared a few years after the start of ARS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…However, their neuroanatomical lesions are various. Although all the patients in these previous studies [8,[17][18][19][20] showed severe degeneration of the globus pallidus, substantia nigra, and subthalamic nucleus, degeneration of the striatum and the brain atrophy were not present or were mild [8,[17][18][19], except in one patient [20]. This last patient showed the marked frontal lobe atrophy and the multiple system degeneration including the striatum that were also observed in patient 1.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…However, their neuroanatomical lesions are various. Although all the patients in these previous studies [8,[17][18][19][20] showed severe degeneration of the globus pallidus, substantia nigra, and subthalamic nucleus, degeneration of the striatum and the brain atrophy were not present or were mild [8,[17][18][19], except in one patient [20]. This last patient showed the marked frontal lobe atrophy and the multiple system degeneration including the striatum that were also observed in patient 1.…”
Section: Discussionmentioning
confidence: 60%
“…4A) of patient 1 appeared similar to respirator-assisted long-survival ALS patients, who progressed into a totally locked-in state [8,[17][18][19][20]. However, their neuroanatomical lesions are various.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…27,28 The reduction of FA in the midpart of the CC and mainly in the cranial parts of the CSTs is probably a result of the prevalent axonal loss within the motor fiber pathway, as was also demonstrated by neuropathologic evidence. 29 Moreover, because the preferential loss of water diffusion in the fiber direction (decreased FA) was not accompanied by higher diffusion perpendicular to the CC fibers (measured by RD) in the body of CC, these effects seem to reflect a wallerian degeneration (atrophy) of the axons rather than a loss of myelin integrity.…”
Section: Discussionmentioning
confidence: 99%
“…29,33 If we take these results together, our data support the hypothesis of an active and at least partially independent bilateral cortical process of degeneration with secondary damage to the CC, particularly in its midbody, known to be significantly involved in the process of axonal degeneration in ALS 34 and substantially formed by interhemispheric fibers connecting the motor cortices, as also demonstrated by diffusion tensor tractography. 35 According to previous neuropathologic findings, 27,34,36 ALS degenerative changes in the cerebral cortex mainly involve motor areas, though recent whole-brain voxel-based morphometry analyses have largely reported GM abnormalities even in extramotor regions. 12,14,15,20,31,37 Thereby, the trends of MD and RD changes, which largely overlapped in our patients in both the genu and splenium of the CC, may represent an increase in the extracellular volume secondary to axonal loss associated with injury to the myelin sheaths, as previously reported in human and animal models of demyelination and axonal degeneration.…”
Section: Discussionmentioning
confidence: 99%